O bullying e suas interferências no processo de ensino - aprendizagem - QUARESMA, Maria Cristina de Almeida (2022)
Among the forms of violence that manifest themselves in the school context, bullying stands out as a phenomenon that implies physical and/or verbal violence practices, occurring recurrently and intentionally against one or more victims. Given this, this Course Conclusion Paper (TCC) discusses the relationship of bullying and its interference in the teaching and learning process. In this way, the theoretical support used is anchored in some scholars who discuss the theme present in the educational context, such as Fante (2005), Gomes (2012), Calhau (2009), Pereira (2002). Bibliographic research is adopted as a methodological procedure, which consists of readings through materials already prepared, including dissertations, articles, books and theses, which create subsidies for the construction of new works on the proposed theme. Thus, the general objective of this study addresses the ways in which bullying manifests itself, and then analyzes how it affects the teaching-learning process of students who are victims of this practice. In other words, through this work it was possible to understand that school violence has always existed and that it can cause damage to the victim's life, it happens both physically and psychologically and as it is something very harmful to the educational environment, it needs to be fought. Since it interferes with the victim's teaching and learning process and consequently harms other areas of their lives, so it is of great importance to make the prevention of this violence more rigorous in our schools.